2007
DOI: 10.1002/jor.20315
|View full text |Cite
|
Sign up to set email alerts
|

Local application of recombinant human fibroblast growth factor‐2 on bone repair: A dose–escalation prospective trial on patients with osteotomy

Abstract: Based on preclinical evidence in animal models, the present study examined the clinical efficacy and safety of recombinant human fibroblast growth factor-2 (rhFGF-2) to accelerate bone repair in a dose-escalation prospective trial. One of three dosages (200, 400 or 800 mg) of rhFGF-2 in a biodegradable gelatin hydrogel was injected during surgery into the osteotomy site of 59 knee osteoarthritis patients undergoing high tibial osteotomy, and 57 of them were monitored for 16 weeks. The rhFGF-2 dose dependently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 37 publications
(58 reference statements)
1
56
0
Order By: Relevance
“…Release of rhFGF-2 from the hydrogel at the site of implantation was measurable for more than 2 weeks, a period that correlates strongly with the patterns of in vivo rhFGF-2 release and hydrogel degradation [18]. One human application that merits attention is a report on single injections of rhFGF-2-impregnated hydrogel at doses of 200, 400, and 800 μg in cut bone surfaces of the lower leg, which produced rapid synostosis in a dosedependent manner [19,20].…”
Section: Discussionmentioning
confidence: 78%
“…Release of rhFGF-2 from the hydrogel at the site of implantation was measurable for more than 2 weeks, a period that correlates strongly with the patterns of in vivo rhFGF-2 release and hydrogel degradation [18]. One human application that merits attention is a report on single injections of rhFGF-2-impregnated hydrogel at doses of 200, 400, and 800 μg in cut bone surfaces of the lower leg, which produced rapid synostosis in a dosedependent manner [19,20].…”
Section: Discussionmentioning
confidence: 78%
“…Based on the evidence of animal studies and a preparatory doseescalation clinical trial, (12)(13)(14)(15)(16)(17)(18) this prospective, randomized, double-blind, placebo-controlled multicenter trial for the first time revealed that local application of a synthetic material, rhFGF-2 hydrogel, accelerated healing of fresh fractures. The hydrogel alone was not likely to affect the healing process because the time to bone union in our placebo group was similar to that without any intervention but the nailing surgery in a previous report.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrogel alone was not likely to affect the healing process because the time to bone union in our placebo group was similar to that without any intervention but the nailing surgery in a previous report. (2) In our previous dose-escalation trial, (18) we selected 0.2, 0.4, and 0.8 mg as the dosages of rhFGF-2 based on results of animal experiments (12,14,17) and found dose-dependent effects on bone union of the tibial osteotomy. (18) To further determine the dosage with maximal efficacy, this study added a dosage of 2.4 mg because our preparatory toxicity tests in dogs with daily intramuscular administration of the rhFGF-2 hydrogel predicted the nontoxic dosage of rhFGF-2 to be 40 mg/kg per day (Supplemental Table S1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Encouraging results have been reported with the use of PRP, bone marrow stromal cells and growth factors [9,19,28], associated both with bone grafting and with bone substitute augmentation. Nevertheless, the use of plasma products still remains experimental and their efficacy compared to autologous iliac crest graft has not been demonstrated yet [9].…”
Section: Debated Issuesmentioning
confidence: 99%